Aposematic coloration does not deter corallivory by fish on the coral Montastraea cavernosa - J. K. Jarett; D. J. Gochfeld; M. P. Lesser (Coral Reefs, 2016)

Environmental drivers of microbial community shifts in the giant barrel sponge, X estospongia muta , over a shallow to mesophotic depth gradient - Kathleen M. Morrow; Cara L. Fiore; Michael P. Lesser (Environmental Microbiology, 2016)
Summary The giant barrel sponge, X estospongia muta , is a high microbial abundance sponge found on Caribbean coral reefs along shallow to mesophotic depth gradients where multiple abiotic factors change with depth. Sponges were collected along a depth gradient at L ittle C ayman ( LC ) and Lee Stocking Island ( LSI ), and the microbiome of these samples was analysed using 16 S r RNA amplicon sequencing. Statistically significant shifts in community structure and dissimilarity (∼ 40%) were detected from 10 to 90 m in LC sponges, but a similar shift was not identified in sponges from 10 to 60 m at LSI (only 17% dissimilar). Additionally, inorganic nutrient levels steadily increased with depth at LSI but not at LC . Based on bulk stable isotopic variability, sponges collected from LC were generally more enriched in 15 N and less enriched in 13 C as depth increased, suggesting a transition from dependency on photoautotrophy to heterotrophy as depth increased. Patterns of stable isotopic enrichment were largely invariant at LSI , which is also reflected in the more stable microbial community along the depth gradient. It appears that environmental factors that change with depth may contribute to differences in X . muta microbial assemblages, demonstrating the importance of contemporaneous environmental sampling in studies of the microbiome of sponges.

Variability in chemical defense across a shallow to mesophotic depth gradient in the Caribbean sponge Plakortis angulospiculatus - Marc Slattery; Deborah J. Gochfeld; M. Cristina Diaz; Robert W. Thacker; Michael P. Lesser (Coral Reefs, 2016)

The effects of heavy load carriage on physiological responses to graded exercise - D. B. Phillips; M. K. Stickland; I. A. Lesser; S. R. Petersen (European Journal of Applied Physiology, 2016)